The Role of Vegetation in Climate Adaptability: Case Studies of Lodz and Warsaw - Hanzl, Małgorzata (2021)
The threats that arise from climate change and their associated economic, social, and environmental impacts are leading to the transformation of the spatial structures of cities. The growing demand for climate adaptability calls for the development of normative criteria for the design of forms of urban settings that integrate vegetation. Climate-responsive urban design reacts to the challenges of urban physics, which depend heavily on the forms of urban structures and the role of greenery. This method includes research on vegetation indexes and their impact on urban regulatory functions. The goal is to propose a comprehensive framework for assessing the functioning of urban public space, which considers the role and maintenance of green infrastructure. The intersection with the subject matter of analytical urban morphology is evident, in terms of the resolution of the urban fabric and its transformations over time. The framework of climate-responsive urban design also covers examining the parameters of surrounding built structures, such as the floor area ratio, the building coverage ratio, and building heights. In particular, the requirements of climate adaptation have an impact on the design of outdoor spaces in cities. In this article, we apply the selected methods that contribute to the climate-responsive urban design model to recommend the transformations of two urban nodes, in Lodz and Warsaw (Poland). Our goal is to indicate the future form of nodal public spaces with a focus on the needs of urban greenery, and to determine indicators for the local climate zone. After an initial literature review, we discuss a number of available indicators from the perspective of how they might contribute to determine the environmental conditions. We focus on urban water cycle, the requirement of trees for water, and insolation conditions.